Cardiac mechanics and dysfunction with anthracyclines in the community: results from the PREDICT study. Issue 1 (16th January 2017) - Narayan, Hari K; Wei, Wei; Feng, Ziding; Lenihan, Daniel; Plappert, Ted; Englefield, Virginia; Fisch, Michael; Ky, Bonnie
Abstract : Background: Our objective was to determine the relevance of changes in myocardial mechanics in diagnosing and predicting cancer therapeutics-related cardiac dysfunction (CTRCD) in a community-based population treated with anthracyclines. Methods: Quantitative measures of cardiac mechanics were derived from 493 echocardiograms in 165 participants enrolled in the PREDICT study (A Multicenter Study in P atients Undergoing AnthR acycline-Based Chemotherapy to Assess the E ffectiveness of Using Biomarkers to D etect and I dentify C ardiotoxicity and Describe T reatment). Echocardiograms were obtained primarily at baseline (prior to anthracyclines), 6 and 12 months. Predictors included changes in strain; strain rate; indices of contractile function derived from the end-systolic pressure–volume relationship (end-systolic elastance (Eessb ) and the left ventricular (LV) volume at an end-systolic pressure of 100 mm Hg (V100 )); total arterial load (effective arterial elastance (Ea)) and ventricular–arterial coupling (Ea/Eessb ). Logistic regression models determined the diagnostic and prognostic associations of changes in these measures and CTRCD, defined as a LV ejection fraction decline ≥10 to <50%. Results: By 12 months, 31 participants developed CTRCD. Longitudinal and circumferential strain and strain rate, V100, Ea, and Ea/Eessb each demonstrated significant diagnostic associations, with a 1–7% increased odds of CTRCD (p<0.05). Changes in longitudinal strain rate (area under the curve (AUC) 0.719 (95% CI 0.595 to 0.843)), V100 (AUC 0.796 (95% CI 0.686 to 0.903)) and Ea (AUC 0.742 (95% CI 0.632 to 0.852)) from baseline to 6 months were individually predictive of CTRCD at 12 months. Conclusions: Changes in non-invasively derived measures of myocardial mechanics are diagnostic and predictive of cardiac dysfunction with anthracycline chemotherapy in community populations. Our findings support the non-invasive assessment of measures of myocardial mechanics more broadly in clinical practice and emphasise the role of serial assessments of these measures during and after cardiotoxic cancer therapy. Trial registration number: NCT01032278 ; Pre-results.